1998
DOI: 10.1177/001440299806400207
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement Effects of an in-Class Service Model on Students with and without Disabilities

Abstract: This article presents the results of a study designed to evaluate the impact of an in-class service model on the achievement of students at risk of school failure. The model, which included collaborative consultation, cooperative teaching, parent involvement, and strategic and adapted instruction was implemented for 1 school year in 13 different schools. Significant effects were found on writing scores for students at risk and on reading and mathematics scores for general education students. No significant tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
0
17
0
8
Order By: Relevance
“…Some educators who have not supported the implementation of IE have questioned the capacity of the system effectively to teach these skills if a student spends a majority of classroom time in academically-focused regular education settings. Saint-Laurent et al (1998) and Hardiman, Guerin and Fitzsimons (2009), who studied children with moderate ID, as well as Cole and Meyer (1991) (who focused on students with severe ID) found no significant differences in the development of adaptive behavior skills of children included in general education classrooms and those attending special classes. Fischer and Meyer (2002) found that a similar group of children with ID and intensive support needs educated in general education settings made significantly larger gains in the development of their adaptive behavior skills than their peers who spent the majority of the day in special classrooms.…”
Section: Academic Outcomesmentioning
confidence: 97%
See 1 more Smart Citation
“…Some educators who have not supported the implementation of IE have questioned the capacity of the system effectively to teach these skills if a student spends a majority of classroom time in academically-focused regular education settings. Saint-Laurent et al (1998) and Hardiman, Guerin and Fitzsimons (2009), who studied children with moderate ID, as well as Cole and Meyer (1991) (who focused on students with severe ID) found no significant differences in the development of adaptive behavior skills of children included in general education classrooms and those attending special classes. Fischer and Meyer (2002) found that a similar group of children with ID and intensive support needs educated in general education settings made significantly larger gains in the development of their adaptive behavior skills than their peers who spent the majority of the day in special classrooms.…”
Section: Academic Outcomesmentioning
confidence: 97%
“…A large number of studies (e.g., Farrell, Dyson, Polat, Hutcheson, & Gallannaugh, 2007) indicate no relationship between academic achievement and inclusion at the district level for students without disabilities and a small relationship at the school level between academic achievement and inclusion. Two studies suggest that when students without disabilities are educated alongside peers with disabilities, they slightly outperform those in non-inclusive settings in math & literacy (Saint-Laurent et al, 1998). In a longitudinal study, Peetsma, Vergeer, Roeleveld and Karsten (2001) found that while there were no initial differences in the academic progress of students with and without mild disabilities even after Abery, Tichá, & Kincade / Moving toward an inclusive education system… 54 two years, by the four-year mark students educated in inclusive settings had made significantly greater academic progress than their matched pairs in special schools.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…Cette option politique et la loi qui la sous-tend 1 reconnaissent comme un droit de l'enfant ayant des besoins particuliers d'être scolarisé dans l'école de sa communauté de domicile. Avec cette réforme, c'est la capacité de l'école à intégrer ces élèves (Bless et Kronig, 1999) qui est interrogée, et non l'efficacité de l'inclusion scolaire (Fisher et Meyer, 2002;Freeman et Alkin, 2000;Hardman et Dawson, 2008;Mitchell, 2008;Saint-Laurent et al, 1998).…”
Section: Contexteunclassified
“…Developed in an inclusive program implemented during one school year in 13 classrooms, the Summary of Individualized Objectives (SIO) was judged to be very useful by special and general education teachers (Saint-Laurent et al, 1998). The SIO presents individualized objectives for each student with academic problems who is placed in an inclusive classroom.…”
Section: Sum M Ary Of Individualized Objectives (Sio)mentioning
confidence: 99%